On the Origin of Sinter‐Resistance and Catalyst Accessibility in Raspberry‐Colloid‐Templated Catalyst Design. (3rd September 2021) - van der Hoeven, Jessi E. S.; Krämer, Stephan; Dussi, Simone; Shirman, Tanya; Park, Kyoo‐Chul K.; Rycroft, Chris H.; Bell, David C.; Friend, Cynthia M.; Aizenberg, Joanna
Abstract: Nanoparticle (NP) sintering is a major cause of the deactivation of supported catalysts. Raspberry‐colloid‐templated (RCT) catalysts are an emerging class of materials that show an unprecedented level of sinter‐resistance and exhibit high catalytic activity. Here a comprehensive study of the origin of NP stability and accessibility in RCT catalysts using theoretical modeling, 3D electron microscopy, and epitaxial overgrowth is reported. The approach is showcased for silica‐based RCT catalysts containing dilute Pd‐in‐Au NPs previously used in hydrogenation and oxidation catalysis. Modeling of the contact line of the silica precursor infiltrating into the assembled raspberry colloids suggests that a large part of the particles must be embedded into silica, which is confirmed by quantitative visualization of >200 individual NPs by dual‐axis electron tomography. The RCT catalysts have a unique structure in which all NPs reside at the pore wall but have >50% of their surface embedded in the matrix, giving rise to the strongly enhanced thermal and mechanical stability. Importantly, epitaxial overgrowth of Ag on the supported NPs reveals that not only the NP surface exposed to the pore but the embedded interface as well remained chemically accessible. This mechanistic understanding provides valuable guidance in the design of stable catalytic materials. Abstract : Raspberry colloid templated (RCT) catalysts are an emerging class of materials, showing an unprecedented level of thermal and catalytic stability compared to conventional catalysts. Quantitative assessment of the metal‐support interfaces of more than 200 particles reveal that substantial nanoparticle embedding in the support underlies the sinter‐resistance of RCT catalysts.